The Influence of Employee Engagement, Self-Efficacy, and Job Stress on Employee Performance with Transformational Leadership as a Moderating Variable among Regionally Owned Enterprises (BUMD) in Kuningan Regency - Nenden Sugiharti; Lili Karmela Fitriani; Dede Djuniardi (IJSM, 2026)
Human resources are a vital asset in achieving organizational goals, especially in Regionally-Owned Enterprises (BUMD). Declining employee performance in BUMDs remains a strategic issue. This study aims to analyze the effects of employee engagement, self-efficacy, and job stress on employee performance and examine the moderating role of transformational leadership. The study employed a quantitative approach with descriptive and verification methods involving 194 respondents using the Slovin technique from three BUMDs in Kuningan Regency (Bank Kuningan, PDAM Tirtakamuning, and PDAU). Data were collected through a semantic differential scale questionnaire and analyzed using Moderated Regression Analysis (MRA) with SPSS 27. The results indicate that: (1) Employee Engagement and Self-Efficacy have a positive and significant effect on Employee Performance; (2) Job Stress has a negative and significant effect on Employee Performance; (3) Transformational Leadership has a positive and significant effect on Employee Performance; (4) Transformational Leadership is able to moderate and strengthen the influence of Employee Engagement and Self-Efficacy on Employee Performance; (5) Transformational Leadership has not been proven to moderate the influence of Job Stress on Employee Performance. These findings indicate that although transformational leadership is effective in increasing motivation and self-confidence, structural interventions are needed to mitigate systemic job stress.